Apoptotic caspases cut down the immunogenicity of radiation - Buqué, Aitziber; Rodriguez-Ruiz, Maria Esperanza; Fucikova, Jitka; Galluzzi, Lorenzo (Oncoimmunology, 2019)
Caspases are known for their ability to precipitate apoptosis. Our findings indicate that accelerating the terminal inactivation of cells dying in response to radiation therapy limit their immunogenicity as a consequence of reduced type I interferon secretion. Thus, caspase inhibitors stand out as promising combinatorial partners to improve the immunogenicity of radiation therapy in the clinic.
Keywords: CGAS; PGE2; mitochondrial outer membrane permeabilization; immune checkpoint blockers; CASP3; SLC7A2